A new welfare regime in the making? Paternalistic welfare pragmatism in China. (February 2019) - Mok, Ka Ho; Qian, Jiwei
Since 2003, the Chinese government has been increasing its social expenditure and initiated new social welfare programmes to provide universal social protection and meet citizens' welfare needs. This article uses the wider socio-economic and socio-political contexts to critically examine whether there is a new welfare regime on the rise in China, with a particular reference to whether the increase in social expenditure has really marked a new welfare philosophy or prompted the transformation of China into a protective welfare regime. By analysing prefecture-level data for government expenditures in education, health, social security and assistance programmes between 2003 and 2012, we show a continuation of the Chinese welfare regime in 'paternalistic welfare pragmatism' for two reasons. First, government social expenditures are set on the basis of the prefecture-level government's fiscal capacity. Second, variations of welfare programmes are associated with the dichotomy between the urban formal and informal sectors.